Communication essentials for dummies - Kuhnke, Elizabeth (--For dummies., 2015)
Utilising a core range of simple skills, this friendly guide shows you how easy it is to communicate effectively. You'll find out how to listen actively, establish rapport, communicate with credibility, manage communication in difficult situations and converse with ease using modern technology - and more. Elizabeth Kuhnke takes the intimidation out of communication by sharing her top tips for successful communication in any situation. You will discover how to get ahead in the workplace by mastering your communication skills; realise the benefits of active listening and the value of establishing rapport; understand how the use of effective communication skills can help you secure a new job offer; recognise how to use effective communication to negotiate your way to personal and professional success. --